Does Investing in Professional Development Coaching for Nurses Help Contribute to Their Better Functioning in The Hospital? - Ramesh, Naveen; John, Dhanya (National Journal of Community Medicine, 2015)
Background: There are not many published studies to assess pro- fessional development among nurses in relation to nursing services provided in different departments of the hospital and also on im- portance of professional development among nursing in India. This prompted the investigator to evaluate the existing profes- sional development program. Objectives of the study were to eval- uate the current professional development training program pro- vided to the nursing staff, assess the role of these professional development training program on nurses and contribution to their functioning and evaluate the impact that the hospital attains through the professional development in nursing. Method: Descriptive cross sectional study which involved one-to- one interview of randomly selected 70 nursing staff working in var- ious departments of a teaching, tertiary care hospital in Bangalore. Results: Most of the participants were young, who had completed GNM Nursing with 2 – 3 years of work experience as staff nurse. Nurses with less education and less experience wanted to learn and know more about recent advances. All participants agreed that professional development classes were beneficial both for their personnel development and in improving their quality of nursing care provided to people. Conclusion: Professional development trainings are beneficial both to the hospital and participants.